Novel carbocationic rearrangements of 1-styrylpropargyl alcohols - Basmadjian, Christine; Zhang, Fan; Désaubry, Laurent (Beilstein Journal of Organic Chemistry, 2015)
The dehydration and subsequent cyclization reactions of 1-styrylpropargyl alcohols was examined. In the course of these studies, numerous scaffolds were synthesized, including a furan, a cyclopentenone, an acyclic enone and even a naphthalenone. The diversity of these structural motifs lies in novel cascades of reactions originating from a common carbocationic manifold.
Keywords: carbocationic rearrangement; cyclopentenones; furans; propargyl alcohols

(untitled) - Boussemart, L.; Malka-Mahieu, H.; Girault, I.; Allard, D.; Hemmingsson, O.; Tomasic, G.; Thomas, M.; Basmadjian, C.; Ribeiro, N.; Thuaud, F.; Mateus, C.; Routier, E.; et al. (Nature, 2014)

(untitled) - Basmadjian, C.; Thuaud, F.; Ribeiro, N.; Désaubry, L. (Future Med. Chem., 2013)

(untitled) - Ribeiro, N.; Thuaud, F.; Bernard, Y.; Gaiddon, C.; Cresteil, T.; Hild, A.; Hirsch, E. C.; Michel, P. P.; Nebigil, C. G.; Désaubry, L. (J. Med. Chem., 2012)

(untitled) - Basmadjian, C.; Zhao, Q.; Désaubry, L. (Tetrahedron Lett., 2015)

(untitled) - An, S. E.; Jeong, J.; Baskar, B.; Lee, J.; Seo, J.; Rhee, Y. H. (Chem. – Eur. J., 2009)

(untitled) - Yang, H.; Fang, L.; Zhang, M.; Zhu, C. (Eur. J. Org. Chem., 2009)

(untitled) - Herrmann, A. T.; Saito, T.; Stivala, C. E.; Tom, J.; Zakarian, A. (J. Am. Chem. Soc., 2010)

(untitled) - Shiroodi, R. K.; Gevorgyan, V. (Chem. Soc. Rev., 2013)

(untitled) - Caruana, P. A.; Frontier, A. J. (Tetrahedron, 2007)

(untitled) - Volchkov, I.; Lee, D. (Chem. Soc. Rev., 2014)

(untitled) - Terao, Y.; Kametani, Y.; Wakui, H.; Satoh, T.; Miura, M.; Nomura, M. (Tetrahedron, 2001)

(untitled) - Bellemin-Laponnaz, S. (ChemCatChem, 2009)